Physiological response and miRNA-mRNA interaction analysis in the head kidney of rainbow trout exposed to acute heat stress. (July 2019) - Zhou, Chang-Qing; Zhou, Peng; Ren, Yan-Li; Cao, Li-Hui; Wang, Jian-Lin
Abstract: The rainbow trout is a cold-water fish cultured in China. Heat stress has a serious impact on the summer survival and the yield of rainbow trout. A better understanding of the regulatory response of rainbow trout to heat stress will help in determining the relationship between heat stress signaling pathways and adaption mechanisms and help contribute to breeding new high-temperature tolerant strains of rainbow trout. In this study, the 48-h median lethal temperature (48h-LT50 ) of rainbow trout was determined as 22.5°C. We developed control (16°C) and heat-treated (22.5°C) groups and extracted RNA from the head kidney tissues for high-throughput sequencing to study the microRNA (miRNA) expression profiles. Twelve up-regulated and five down-regulated miRNAs were identified between the control and heat-treated groups. A total of 22 target genes were predicted for 6 of the differentially expressed miRNAs, including 31 negative miRNA–mRNA interactions. Important regulatory pathways under heat stress are related to the metabolism and immune responses of the rainbow trout. Our findings provide preliminary data for investigating the high-temperature molecular mechanism of the rainbow trout and can help producers to reduce the economic losses caused by high temperature weather. Highlights: 48 h median lethal temperature (48h-LT50 ) of rainbow trout was determined as 22.5°C. 12 up regulated and 5 down regulated miRNAs were associated with regulation of heat stress in rainbow trout. Important regulatory pathways under heat stress are related to the metabolism and immune responses of the rainbow trout.